Ultrasound Estimates of Visceral and Subcutaneous-Abdominal Adipose Tissues in Infancy - Emanuella De Lucia Rolfe; Neena Modi; Sabita Uthaya; Ieuan A. Hughes; David B. Dunger; Carlo Acerini; Ronald P. Stolk; Ken K. Ong (Journal of Obesity)
Other imaging techniques to quantify internal-abdominal adiposity (IA-AT) and subcutaneous-abdominal adiposity (SCA-AT) are frequently impractical in infants. The aim of this study was twofold: (a) to validate ultrasound (US) visceral and subcutaneous-abdominal depths in assessing IA-AT and SCA-AT from MRI as the reference method in infants and (b) to analyze the association between US abdominal adiposity and anthropometric measures at ages 3 months and 12 months. Twenty-two infants underwent MRI and US measures of abdominal adiposity. Abdominal US parameters and anthropometric variables were assessed in the Cambridge Baby Growth Study (CBGS), infants (23 girls) at age 3 months and infants (237 girls) at 12 months. US visceral and subcutaneous-abdominal depths correlated with MRI quantified IA-AT (, ) and SCA-AT (, ) volumes, respectively. In CBGS, mean US-visceral depths increased by 20 % between ages 3 and 12 months () and at both ages were lower in infants breast-fed at 3 months than in other infants. US-visceral depths at both 3 and 12 months were inversely related to skinfold thickness at birth ( and at 3 and 12 months, resp.; adjusted for current skinfold thickness). In contrast, US-subcutaneous-abdominal depth at 3 months was positively related to skinfold thickness at birth (). US measures can rank infants with higher or lower IA-AT and SCA-AT. Contrasting patterns of association with visceral and subcutaneous-abdominal adiposities indicate that they may be differentially regulated in infancy.